Society in the Digital Era: Adaptation, Change, and Response to Communication Technology - Ganiem, Leila Mona; Setiawati, Rahmi; Suardi, Suardi; Nurhayai, Nurhayai; Ramdhani, Rahmat (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2024)
In the current digital era, communication technology has gradually changed the social landscape. Society faces pressure to adapt to rapid technological developments, which can affect interaction and communication patterns. This research aims to investigate how society adapts, experiences change, and responds to communication technology in the context of the digital era. The focus is to understand the impact of technology on social dynamics, as well as the strategies used by individuals and communities in dealing with these changes. This research method was carried out through a qualitative approach, using in-depth interviews and participant observation to collect data. The research sample was selected purposively, covering various different levels of society in the context of communication technology. The research results show that society experiences various levels of adaptation to communication technology, from acceptance to resistance. Changes in communication and social interaction patterns were identified, along with the adoption of new technologies and shifts in cultural values. The conclusions of this research illustrate the complexity of social dynamics in the digital era, where adaptation, change and response to communication technology play a key role in shaping patterns of human interaction. A deeper understanding of these processes can help in developing more effective strategies for managing the impact of technology in modern society